Jacaranda SOSE studies of society & environment : national profiles & the curriculum and standards framework : history - Cotter, Richard (Jacaranda Wiley, 1997)
Jacaranda SOSE History is written specifically for level 6 of the National Profiles and the Curriculum and Standards Framework. The text comprehensively covers the 'Time, Continuity and Change' and 'Culture' strands as well as providing approaches to other Studies of Society and Environment outcomes.